Menata Ulang Pembagian Wewenang Pengawasan Hakim - Faiz, Elza (Universitas Islam Indonesia, 2026)
Finding an equilibrium point between judicial independence and judicial accountability is a key challenge in designing a judicial oversight system. This balance requires an institutional structure capable of clearly dividing oversight authority. To this date, existing studies have not provided an adequate structure regarding the division of oversight authority between the Supreme Court and the Judicial Commission. This study examines the problematic division of oversight authority between the Supreme Court and the Judicial Commission within the framework of maintaining a balance between judicial independence and accountability. Although both institutions have been normatively mandated to oversee their respective authorities, their implementation has not been optimal due to several legal issues in their regulations. This study uses a normative-empirical legal method through an analysis of laws and regulations, institutional documents, and empirical data regarding the implementation of judicial oversight. The results indicate that the unclear division of authority is a major factor contributing to the ineffectiveness of judicial oversight in realizing judicial accountability. The results indicate that suboptimal oversight is caused by the weak binding power of the Judicial Commission's recommendations and the unclear boundaries between judicial technicalities or legal errors and codes of ethics or judicial misconduct. The novelty of this research lies in the development of the Shared Authority System, which emphasizes the division of supervisory authority between the Supreme Court and the Judicial Commission and introduces the Joint Classification Forum as a mechanism for resolving areas of overlap between judicial technical matters and judicial ethical violations. This model provides a clearer institutional framework to strengthen judicial accountability without compromising judicial independence.